MUSLIM-CHRISTIAN MARRIAGE IN NORTHERN NIGERIA: AN EVALUATION OF CONFLICT RESOLUTION STRATEGIES FOR MANAGING CAT-DOG RELATIONSHIP. - Jamo, Maryam Suleiman; Özad, Bahire Efe; Uygarer, Gulen (TRAMES: A Journal of the Humanities & Social Sciences, 2024)
Generally, the relationship between Muslims and Christians in Nigeria, especially northern Nigeria, is dysfunctional, antagonistic, tense, aggressive, and violent. Thus, management of Muslim-Christian marital relationship in such society requires effective communication and conflict resolution strategies. However, Muslim-Christian interfaith marriages exist and flourish in the country. Therefore, this study evaluates conflict resolution strategies in relationships among Muslim-Christian couples in northern Nigeria. The study is guided by Rational Dialectics Theory (RDT). Triangulation has been employed and the data have been gathered through semi-structured interviews, observation, and field notes with phenomenology as the approach. Using snowball sampling technique, 30 people - 19 females and 11 males who are into Muslim-Christian marriage were interviewed, as participants in the study. The findings revealed that conflict in a relationship is inevitable but the most effective conflict resolution strategies used in managing interreligious marital relationship include embracing dialogic communication, being engaged in positive and supportive communication, interpersonal communication, and then upholding interest, affection, gratitude, and apologies. The present study concludes that conflict in a relationship does not always indicate a problem, rather, it is a means where married individuals can understand themselves better and work towards resolving the differences that cause dispute.